GA Optimization of the Optical Directional Coupler - Ozkan-Bakbak, Pinar (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2017)
Optical couplers, which are passive devices, couple optic waves through optical waveguides and can be employed in many applications, including power splitters, optical switches, wavelength filters, polarization selectors, etc. In this work, a simple, fast and instant optimization design is presented for an optical directional coupler based on Genetic Algorithms (GA). This optimization design is preferred due to its favourable usage and fast convergence capability. Finally, the designed methodology has been analytically and experimentally evaluated and the results show that the GA is an advantageous method for designing an optical element where the measurable data is obtainable instead of complex formulas.
Keywords: Genetic Algorithm; optical directional coupler; Engineering; Telecommunications